Patient-reported outcomes in patients undergoing elective arthroplasty: the PaRIS-IOR study. (30th September 2020) - Golinelli, D; Rosa, S; Rucci, P; Tedesco, D; Grassi, A; Amabile, M; Cosentino, M; Maietti, E; Zaffagnini, S; Fantini, M P
Abstract: Background: The number of hip and knee arthroplasties continues to rise worldwide. The Organization for Economic Cooperation and Development has launched the PaRIS Initiative for the systematic collection of Patient Reported Outcome Measures (PROMs) in patients undergoing elective hip and knee arthroplasty. The Rizzoli Orthopedic Institute (IOR) was selected as a pilot center for the Initiative (PaRIS-IOR study), because it hosts the Registry of Orthopedic Prosthetic Implants (RIPO). The objective of PaRIS-IOR study is to investigate the characteristics and temporal trend of PROMs in relation to the type of surgical intervention and patient profile. Here we report the preliminary results of the first study year. Methods: The PaRIS-IOR is a prospective, single site, cohort study started on January 1st 2019 that consists of the administration of Euro Quality 5 Dimensions (EQ-5D), Hip disability and Osteoarthritis Outcome Score and Knee injury and Osteoarthritis Outcome Score Physical function Short-form (HOOS-PS, KOOS-PS) questionnaires to patients on the list for elective arthroplasty. Questionnaires data are linked with those routinely collected by the RIPO and regional administrative data, in order to track patients' medical history. Results: The study population consists of 1, 413 patients. Patients undergoing knee arthroplasty (n = 393) were older (68.4 vs 60.2 years; p < 0.001), and had a higher prevalence of obesity (41.6 vs 22.6%; p < 0.001) than patients undergoing hip arthroplasty (n = 1020). Female and obese patients reported a worse perceived health status both in the EQ-5D (p < 0.001) and in the HOOS-PS and KOOS-PS (p < 0.001). Among patients who underwent knee surgery, the younger ones reported a poorer perceived health in the general and the specific questionnaires. Conclusions: The PaRIS-IOR study has potential important implications in targeting the factors affecting patient-reported functional outcomes and quality of life after joint arthroplasty. Key messages: The PaRIS-IOR study underscores the poorer perception of health status in female and obese patients undergoing arthroplasty and in younger patients undergoing knee surgery. The routine adoption of PROMs may support surgeons in the management of patients undergoing hip and knee arthroplasty and policy-makers in improving healthcare quality in orthopedics.